Modulation of STAT-1, STAT-3, and STAT-6 activities in THP-1 derived macrophages infected with two Trypanosoma cruzi strains - Oliveira, Melissa Martins; Bonturi, Camila Ramalho; Salu, Bruno Ramos; Oliva, Maria Luiza Vilela; Mortara, Renato Arruda; Orikaza, Cristina Mary (Frontiers in Immunology, 2022)
Trypanosoma cruzi is the causative protozoan of Chagas’ Disease, a neglected tropical disease that affects 6‒7 million people worldwide. Interaction of the parasite with the host immune system is a key factor in disease progression and chronic symptoms. Although the human immune system is capable of controlling the disease, the parasite has numerous evasion mechanisms that aim to maintain intracellular persistence and survival. Due to the pronounced genetic variability of T. cruzi, co-infections or mixed infections with more than one parasite strain have been reported in the literature. The intermodulation in such cases is unclear. This study aimed to evaluate the co-infection of T. cruzi strains G and CL compared to their individual infections in human macrophages derived from THP-1 cells activated by classical or alternative pathways. Flow cytometry analysis demonstrated that trypomastigotes were more infective than extracellular amastigotes (EAs) and that strain G could infect more macrophages than strain CL. Classically activated macrophages showed a lower number of infected cells and IL-4-stimulated cells displayed increased CL-infected macrophages. However, co-infection was a rare event. CL EAs decreased the production of reactive oxygen species (ROS), whereas G trypomastigotes displayed increased ROS detection in classically activated cells. Co-infection did not affect ROS production. Monoinfection by strain G or CL mainly induced an anti-inflammatory cytokine profile by decreasing inflammatory cytokines (IFN-, TNF-, IL-1) and/or increasing IL-4, IL-10, and TGF-. Co-infection led to a predominant inflammatory milieu, with reduced IL-10 and TGF- and/or promotion of IFN- and IL-1 release. Infection by strain G reduced activation of intracellular signal transducer and activator of transcription (STAT) factors. In EAs, monoinfections impaired STAT-1 activity and promoted phosphorylation of STAT-3, both changes may prolong cell survival. Coinfected macrophages displayed pronounced activation of all STATs examined. These activations likely promoted parasite persistence and survival of infected cells. The collective results demonstrate that although macrophages respond to both strains, T. cruzi can modulate the intracellular environment, inducing different responses depending on the strain, parasite infective form, and co-infection or monoinfection. The modulation influences parasite persistence and survival of infected cells.